Ambiguous Utterances: Case Study On Students’ Project Of English Presentation - Ozi Satria Rina Lisfianti (Al-Faiza : Journal of Islamic Education Studies, 2023)
This research purposed to identify the types of ambiguous utterances particularly lexical ambiguity employed by college students on presentation projects of English subjects and to recognize the possible factors which caused the students’ presented ambiguous utterances on their presentation. This research implied descriptive qualitative with a case study approach. In which, the researcher employed observation, interview, and documentation as techniques of data collection. Thence, to analyze the data the researcher used three steps based on Miles and Huberman theory such as, the researcher did data reduction, displayed the data as some categories, and the last step manufactured the conclusion. To answer both research focus the researcher adopted Cruse Laporte theory. From the two types of lexical ambiguity, the researcher only found homonyms such as “I look at the duck” presented by the student “HH”, “We will miss the unique cat” presented by the student “EW”, “One of my friends hold the bat” was employed by the student “JA”, “There was a Kecial bird on my back” was uttered by the student “JU”, “I like this season so much” was uttered by the student “YK”, and the last one was said by the student “IG” it was “I am still young”. These homonyms were caused by some factors they were 2 students felt “No knowledge of English”, 7 students felt “no context comprehension”, 6 students owned “limited vocabulary”, and the last factor was “no knowledge of English structure” explained by 5 students. Those results were significantly described as valuable contributions in relation to providing updated knowledge of ambiguous utterances especially lexical ambiguity employed by the college students on presentation projects of English Subjects.